Gestión comercial de la empresa pública municipal de Saneamiento Ambiental de Babahoyo EMSABA EP - Mora Álava, Nathali Belén (2021)
The present work is directed to the sub-line of research of the Commercial Engineering career called "Marketing and Commercialization", the factors that affect the commercial management of EMSABA EP were determined, for which a Qualitative methodology was applied that allows working in a context structural and also situational. In the case study, the inductive method was used that allowed starting from specific facts to reach general conclusions of the research, techniques such as the survey and the interview were applied; the first applied to the users of the company and the interview with the person in charge of the commercial area of EMSABA EP. A questionnaire was developed with open questions for the interview and a structured questionnaire for the survey.